PENGARUH RASIO PASAR PERUSAHAAN TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI SEKTOR INDUSTRI DASAR & KIMIA BURSA EFEK INDONESIA TAHUN 2017-2021) - Koeswara, Dicky; Syaifuddin, Dedy Takdir; Budi, Nuryamin; Madi, Riski Amalia; Oktaviani, Unika (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2023)
Investors invest to maximize returns by taking into account the investment risk factors they will face. Return is the main factor that motivates investors to invest and as a reward for the courage of investors to take the investment risks that have been taken. This study was conducted to examine the effect of market ratios on stock returns on Manufacturing stocks that have positive dividends during the period 2017 to 2021. The number of samples studied was fifty-four (54) companies selected through the purposive sampling method. The data collection method used in this research is the Documentation method. Data analysis was carried out using multiple linear regression analysis techniques. The results of the analysis found that market ratios proxied by PBV, PER, and EPS have a positive and insignificant effect on stock returns and DPR has a negative and significant effect on stock returns.